(untitled) (Jurnal Teknologi Industri Pertanian, 2016)
Sausages is a nutritious and perishable food so that it needs treatment to extent the shelf life. The aim of this research was to find out the effect of kaffir lime leave oleoresin on beef sausage quality such as microbiological and physicochemical characteristic during frozen storage (-10±2°C). The completely Randomized Design (CRD) was used with one factor was the concentration of kaffir lime leave oleoresin in edible packaging at 0%, 0.05%, and 0.15%.. The observations were done more 0, 1, 2, 3, and 4 months. The results showed that the addition of kaffir lime leave oleoresin on edible packaging affect the beef sausage quality. With lower amount of microbes and more stabilize color of beef sausage. The increase of kaffir lime leave oleoresin decreased TVB and pH value of beef sausage. Keywords: beef sausage, Citrus hystrix, edible packaging, oleoresin